1981
DOI: 10.1136/bmj.282.6272.1259
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro venous prostacyclin production, plasma 6-keto-prostaglandin F1 alpha concentrations, and diabetic retinopathy.

Abstract: Previous studies have shown that vessels from diabetics produce less prostacyclin in vitro than those from normal controls. To determine whether this decreased production is related to complications elective biopsy of a superficial forearm vein was performed on 12 insulin-dependent male diabetics, six with nil or minimal and six with proliferative retinopathy, and seven male controls. Vein segments from the diabetics and controls produced similar amounts of prostacyclin in vitro (medians 011 and 0 19 ng/mg tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In healthy people, physical exercise increases the plasma or urinary level of 6-keto-PGF ltt , a stable metabolite of PCI 2 (2-5). This finding is consistent during long-term exercise, whereas unchanged plasma levels have also been observed during acute exercise (6).Plasma concentration of TXB 2 , a metabolite of TXA 2 , is shown to increase (7) or remain the same (4,8,9) during exercise in healthy people.In diabetic patients in the resting state, PGI 2 production, as assessed by 6-keto-PGF 1a concentrations in plasma or urine, has been either decreased (10-13), increased (14-16), or normal (17,18). In most studies, plasma TXB 2 levels or TXB 2 production from platelets in vitro is increased in diabetes (16,(19)(20)(21)(22), although normal levels have also been reported (17).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In healthy people, physical exercise increases the plasma or urinary level of 6-keto-PGF ltt , a stable metabolite of PCI 2 (2-5). This finding is consistent during long-term exercise, whereas unchanged plasma levels have also been observed during acute exercise (6).Plasma concentration of TXB 2 , a metabolite of TXA 2 , is shown to increase (7) or remain the same (4,8,9) during exercise in healthy people.In diabetic patients in the resting state, PGI 2 production, as assessed by 6-keto-PGF 1a concentrations in plasma or urine, has been either decreased (10-13), increased (14-16), or normal (17,18). In most studies, plasma TXB 2 levels or TXB 2 production from platelets in vitro is increased in diabetes (16,(19)(20)(21)(22), although normal levels have also been reported (17).…”
mentioning
confidence: 93%
“…In diabetic patients in the resting state, PGI 2 production, as assessed by 6-keto-PGF 1a concentrations in plasma or urine, has been either decreased (10)(11)(12)(13), increased (14)(15)(16), or normal (17,18). In most studies, plasma TXB 2 levels or TXB 2 production from platelets in vitro is increased in diabetes (16, [19][20][21][22], although normal levels have also been reported (17).…”
mentioning
confidence: 98%
“…56 Prostacyclin production by blood vessels from patients with diabetes is depressed 57 and circulating levels of 6-oxo-PGF la are reduced in diabetic patients with proliferative retinopathy. 58 Davis and colleagues 59 have confirmed that vessels taken from diabetic patients produced less prostacyclin than from normal subjects. However, their results did not support an association between reduced prostacyclin production and diabetic retinopathy.…”
Section: Prostacyclin and Txa 2 In Diseasementioning
confidence: 91%
“…It is possible that the reduced vascular resistance and hypotension of DKA may be due, at least in part, to the vasodilatation caused by elevated circulating levels of PGI 2 . Although PGI 2 production from endothelium of large blood vessels is decreased in diabetes mellitus (9)(10)(11)(12), PGI 2 production by adipose tissue is increased in the absence of insulin (13,14). This suggests that adipose tissue is the principal source of the elevated circulating PGI 2 concentration in DKA.…”
mentioning
confidence: 90%